2014
DOI: 10.1002/ange.201310940
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organo‐Photocatalysis Mediated by Atropisomeric Thiourea Derivatives

Abstract: Can photocatalysis be performed without electron or energy transfer? To address this, organo-photocatalysts that are based on atropisomeric thioureas and display lower excited-state energies than the reactive substrates have been developed. These photocatalysts were found to be efficient in promoting the [2+2] photocycloaddition of 4-alkenyl-substituted coumarins, which led to the corresponding products with high enantioselectivity (77-96 % ee) at low catalyst loading (1-10 mol %). The photocatalytic cycle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…They designed a chiral thiourea 322 , which can act as hydrogen-bonding template to activate coumarin 319 ( Scheme 104 ). 597 …”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
“…They designed a chiral thiourea 322 , which can act as hydrogen-bonding template to activate coumarin 319 ( Scheme 104 ). 597 …”
Section: Direct Excitation and Sensitizationmentioning
confidence: 99%
“…Other strategies for the enantioselective catalysis of photochemical processes 15,92 have been successively developed. For example, it was demonstrated that a mechanistically similar intramolecular [2+2] photocycloaddition is promoted with high stereoselectivity by chiral thiourea catalysts 93 , traditional ground-state hydrogen-bonding organocatalysts 94 .…”
Section: Noncovalent Activation In Asymmetric Photochemistrymentioning
confidence: 99%
“…The first highly enantioselective photoreactions were not developed until the early 2000s, 13 and only a handful of successful of alternative strategies have emerged since then. 14,15,16 The slow rate of development in this field is particularly surprising considering the rapid rate at which asymmetric catalytic methods were developed for so many other, nonphotochemical reaction types in the last decades of the 20 th century.…”
Section: Introductionmentioning
confidence: 99%